Perceptive Transformations in Consumer Payment Behaviors – Do Arming With Online Technology Attracts Consumers? Exploring the Impact of Online Technology on Consumer Payment Behaviors in India (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Advancement of technology and innovation made huge development and opened a door of opportunities for digital payment in India and the digital wallet, organizations profited the opening such doors. Digital payment has revolutionized retailing by making consumers buying different products from all over the world. In the last decade, India has witnessed huge growth in the use of mobile phones in the digital India era. This expanding utilization of the web, versatile use of mobile phones, and government endeavors combined with the widespread use of digital payment modes, for example, Google Pay, Paytm, etc. have shifted the consumer base towards the use of more and more digital modes.